The mechanism of tetraploidization in tree peony, and its implications for speciation and evolution of genus Paeonia L. - Zhong, Yuan; Du, Ming-jie; Ji, Run-ze; Cheng, Fang-yun (Frontiers in Plant Science, 2025)
IntroductionPolyploidization is not only an important driving force for plant speciation and evolution, but also an effective approach for plant domestication and improvement. Polyploid taxa are quite common in Paeonia section Paeonia (herbaceous peonies), but very rare in section Moutan (tree peonies), which are known as the ‘king of flowers’.MethodsIn this paper, we studied the origination of a tetraploid tree peony, P. × lemoinei ‘Golden Era’ (‘GE’, AABB), by comparing its karyotype with its seed parent, P. × lemoinei ‘Golden Isles’ (‘GI’, AB), based on genomic in situ hybridization (GISH) and rDNA fluorescence in situ hybridization (FISH). The meiosis behaviors of ‘GI’ were observed to make clear the cytogenetic process of unreduced (2n) gamete generation.ResultsFour chromosomes with inter-genome translocations were identified in ‘GE’, two of which might be reciprocal translocations. The 2n female gametes via first division restitution (FDR) from ‘GI’ might play an important role in tetraploidization of ‘GE’.DisucssionThe distant hybridization between intersterile species from different subsections of section Moutan probably promotes the tetraploidization of tree peonies by facilitating 2n gamete production. The mechanism of tetraploidization in section Moutan is highly consistent with that in section Paeonia, but is inseparable with the assist from mankind. The divergence of life history between tree peonies and herbaceous peonies is speculated to contribute to the different level of polyploidization, and distinct tempo of speciation and evolution, between section Moutan and section Paeonia in genus Paeonia. These findings bring new insights to polyploid breeding, speciation and evolution in genus Paeonia.